2021
DOI: 10.1016/j.ygeno.2020.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and genomics of SARS-CoV-2: A review of the literature with the special focus on genetic diversity and SARS-CoV-2 genome detection

Abstract: The outbreak of 2019-novel coronavirus disease (COVID-19), caused by SARS-CoV-2, started in late 2019; in a short time, it has spread rapidly all over the world. Although some possible antiviral and anti-inflammatory medications are available, thousands of people are dying daily. Well-understanding of the SARS-CoV-2 genome is not only essential for the development of new treatments/vaccines, but it also can be used for improving the sensitivity and specificity of current approaches for virus detection. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 159 publications
1
125
0
3
Order By: Relevance
“…[ 10 ] The number and incidence of mutations are much higher in Europe and North America compared with Asia, which also indicates different mutation patterns. [ 11 ] A high-throughput and high-coverage SARS-CoV-2 complete genome sequence study has observed that distinct time-course evolution patterns are divided into four main mutation groups. [ 12 ] Two nonsynonymous mutations A23403G and C14408T are mainly from Europe and North America, one nonsynonymous mutation T28144C is mainly distributed in Asia and Spain, two nonsynonymous mutations G11083T and G26144T are mainly distributed in Asia and some European countries, while two other nonsynonymous mutations G1440A and G2891A are mainly found in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] The number and incidence of mutations are much higher in Europe and North America compared with Asia, which also indicates different mutation patterns. [ 11 ] A high-throughput and high-coverage SARS-CoV-2 complete genome sequence study has observed that distinct time-course evolution patterns are divided into four main mutation groups. [ 12 ] Two nonsynonymous mutations A23403G and C14408T are mainly from Europe and North America, one nonsynonymous mutation T28144C is mainly distributed in Asia and Spain, two nonsynonymous mutations G11083T and G26144T are mainly distributed in Asia and some European countries, while two other nonsynonymous mutations G1440A and G2891A are mainly found in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…22 The UK variant was also found to have impact on diagnosis of SARS-CoV-2 as the deletion mutations in 69-70 can cause negative result from S-gene in RT-PCR assay. [23][24][25][26] Mutations in the RBD of spike protein or other surface structures can alter the antigenic property of new SARS-CoV-2 variant that could lead to reduction in neutralization activity of antibodies and thereby resulting in higher risk of reinfection or decreased effectiveness of vaccines. 27 Therefore, there is an urgent need to study the mutation pattern of SARS-CoV-2 and mechanism of virulence or pathogenesis of new variant B.1.1.7 to develop effective therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2는 Coronaviridae 과(family)에 속하는 바이러스로 2019년 중국 중부지 역 후베이성의 주도인 우한시에서 처음 발견된 신종바이러스이다. Coronaviridae 과에 nm 정도로 비교적 크기가 큰 편이며, 호흡기 바이러스의 대표적인 인플루엔자바이러스(influenza virus)는 80-120 nm 정도의 크기이 다 [1,2]. 반면 소화기 감염을 일으키는 RNA 바이러스인 rotavirus 는 70-75 nm 크기에 18.5 kb의 유전자를 가지고 있으며, norovi-rus는 27-40 nm 크기에 7.5-7.7 kb의 유전자 크기를 가지고 있다 [3].…”
Section: Sars-cov-2의 분류 및 유전자 구조unclassified